Investigating factors relevant to a multicultural HIV/AIDS Curriculum for Assemblies of God - Johns, Emily M. Busiek (Stellenbosch : University of Stellenbosch, 2009)
Thesis (PhD (Curriculum Studies))--University of Stellenbosch, 2009.